Bovine endometrial cells: a source of mesenchymal stem/progenitor cells - de Moraes, Carolina Nogueira [UNESP]; Maia, Leandro [UNESP]; Dias, Marianne Camargos [UNESP]; Dell'Aqua, Camila P. Freitas [UNESP]; da Mota, Ligia Souza Lima Silveira [UNESP]; Chapwanya, Aspinas; Landim-Alvarenga, Fernanda da Cruz [UNESP]; Oba, Eunice [UNESP] (Wiley, 2016)
Endometrial mesenchymal stem/progenitor cells (eMSCs) are multipotent cells known to modulate the immune system and have clinical application for human and animal health. This makes these bovines cells attractive for dual use as cellular therapy and experimental model. The aim of this study was to isolate, evaluate the differentiation potential, immunophenotypic and immunocytochemistry characteristics, chromosomal stability, cloning efficiency, and cryopreservation response of bovine eMSCs collected in two phases of the estrous cycle. For this, cells were isolated and submitted to differentiation for adipogenic and osteogenic lineage. The cells were then characterized by flow cytometer (FC) (vimentin, CD29, CD44, MHC-II, CD34) and immunocytochemistry (vimentin, pan-cytokeratin, CD44) and submitted to cytogenetic and cloning efficiency assay. The cells were also cryopreserved using two different medium of cryopreservation and analyzed by FC for viability, necrosis, late-apoptosis + necrosis, and initial apoptosis rates before and after cryopreservation. We obtained homogeneous cell populations which have fibroblastic morphology and adherence to plastic. These cells expressed high levels of markers CD29, CD44, and vimentin, low expression levels for CD34 and no MHC-II. The cells were chromosomally stable (2n = 60) with high cloning efficiency and no difference (P > 0.05) between medium of cryopreservation or phase was observed after thawing. We showed the presence and differentiation potential of bovine eMSCs, with chromosomal stability and great response to cryopreservation with both medium, which has implications for build biobanks or development of new therapeutic approaches to combat uterine diseases or to study.
Keywords: characterization; cow; cryopreservation; endometrium; progenitor cells